Implementation of the parametric representation of the Fourier transform in fabrics (2007)
The periodic nature of textile fabric images allows the use of fast Fourier transformation techniques for classification. Due to the repetition patterns within the images of the textile fabric, it is possible to find a relatively easy way of description for their spectral energy density. A previously published work allows to show the use of descriptors for the Fourier spectrum of the images, in particular their efficiency to the invariance to the rotation, translation and change of scale [1].